Corporate Investment in Emerging Markets : Financing vs. Real Options Channel - Li, Delong (IMF Working Papers; Working Paper ;, 2015)
We examine how firm and country heterogeneity shape the response of corporate investment in emerging markets to changes in global interest rates and volatility. We test for the presence of (i) a financing channel originating from changes in the costs of external borrowing and (ii) a real options channel-reflecting firms' option values to delay investment. We find evidence of the coexistence of both channels. Financially weaker firms reduce investment by more in response to higher interest rates or volatility, while firms with stronger balance sheets become less willing to invest after volatility spikes. Furthermore, the intensity of the financing channel diminishes for firms in countries with lower public debt, higher foreign reserves, or deeper financial markets.